2004
DOI: 10.1016/s0896-6273(04)00191-6
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Oscillations at α and θ Frequencies in the Lateral Geniculate Nucleus

Abstract: In relaxed wakefulness, the EEG exhibits robust rhythms in the alpha band (8-13 Hz), which decelerate to theta (approximately 2-7 Hz) frequencies during early sleep. In animal models, these rhythms occur coherently with synchronized activity in the thalamus. However, the mechanisms of this thalamic activity are unknown. Here we show that, in slices of the lateral geniculate nucleus maintained in vitro, activation of the metabotropic glutamate receptor (mGluR) mGluR1a induces synchronized oscillations at alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
350
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(392 citation statements)
references
References 43 publications
(1 reference statement)
37
350
1
4
Order By: Relevance
“…Indeed, the particular effectiveness of electrical synapses at transmitting lowfrequency events (Landisman et al, 2002;Long et al, 2004) makes them ideally suited to this role. A similar scenario might also exist for TC neurons (Hughes et al, 2004), where electrical synapses are also present (Hughes et al, 2002b), raising the prospect that a certain degree of slow (Ͻ1 Hz) wave synchronization can occur locally in the thalamus.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, the particular effectiveness of electrical synapses at transmitting lowfrequency events (Landisman et al, 2002;Long et al, 2004) makes them ideally suited to this role. A similar scenario might also exist for TC neurons (Hughes et al, 2004), where electrical synapses are also present (Hughes et al, 2002b), raising the prospect that a certain degree of slow (Ͻ1 Hz) wave synchronization can occur locally in the thalamus.…”
Section: Discussionmentioning
confidence: 85%
“…Under control conditions, most TC neurons fired rarely and irregularly, but, when they did so, firing was predominantly of the low-threshold burst firing type (83.3%; n ϭ 5 of 6 units) (Fig. 7A 1 ,B) (Hughes et al, 2004). In contrast, units recorded in the presence of 50 nM GBZ predominantly exhibited tonic rather than low-threshold burst firing (94.4%; n ϭ 17 of 18 units) (Fig.…”
Section: Preferential Block or Enhancement Of The Tonic Current Modulmentioning
confidence: 91%
“…Physiological significance TC neurons can exhibit three modes of firing: low-threshold bursting driven by low-threshold Ca 2ϩ spikes; tonic firing consisting of repetitive single action potentials; and high-threshold bursting mediated by high-threshold, probably T-type channeldependent, Ca 2ϩ spikes (Jahnsen and Llinás, 1984;Crunelli et al, 1989;Hughes et al, 2004). Tonic and high-threshold bursting occur at relatively depolarized membrane potentials, whereas low-threshold bursting occurs at hyperpolarized membrane potentials, with a region of quiescent membrane potential in between.…”
Section: Properties Of the Tonic Gaba A Currentmentioning
confidence: 99%
“…(3) Bursting thalamic relay neurons exert a rhythmic influence on thalamocortical modules in the theta frequency band (Hughes et al, 2004). The tight anatomical (Van Horn et al, 2000) and functional coupling between the thalamus and cortex is confirmed by the high theta coherence between the two (Fig.…”
Section: Mechanism Of Pd Symptomsmentioning
confidence: 95%